GE_GERICHTE P/17737/2017 vom 26. April 2018 - GE Cour de justice (2018)
USAGE ABUSIF ; CONTRAINTE(DROIT PÉNAL) ; COMPÉTENCE RATIONE LOCI ; IMMUNITÉ ; HARCÈLEMENT SEXUEL(DROIT DU TRAVAIL) ; PERSÉCUTION | CP.179.alsepties; CP.3; CP.181; CPP.310.al1.leta; CPP.310.al1.letb